Residual High-Grade Stenosis After Recanalization of Extracranial Carotid Occlusion in Acute Ischemic Stroke. Issue 1 (January 2015) - Luitse, Merel J.A.; Velthuis, Birgitta K.; Dauwan, Meenakshi; Dankbaar, Jan Willem; Biessels, Geert Jan; Kappelle, L. Jaap; Majoie, C.B.; Roos, Y.B.; Duijm, L.E.; Keizer, K.; van der Lugt, A.; Dippel, D.W.; et al.
Abstract : Background and Purpose—: Residual stenosis after recanalization of an acute symptomatic extracranial occlusion of the internal carotid artery (ICA) might be an indication for carotid endarterectomy. We evaluated the proportion of residual high-grade stenosis (≥70%, near occlusions not included) on follow-up imaging in a consecutive series of patients with an acute symptomatic occlusion of the extracranial ICA. Methods—: We included patients participating in the Dutch Acute Stroke Study (DUST), who had an acute symptomatic occlusion of the extracranial ICA that was diagnosed on computed tomographic angiography within 9 hours after onset of neurological symptoms. Follow-up imaging of the carotid artery had to be available within 7 days after admission. Results—: Of the 1021 patients participating in DUST between May 2009 and May 2013, an acute symptomatic occlusion of the extracranial ICA was found in 126 (12.3%) patients. Follow-up imaging was available in 86 (68.3%) of these patients. At follow-up, a residual stenosis of <30% was found in 15 (17.4%; 95% confidence interval, 10.8–26.9) patients, a 30% to 49% stenosis in 3 (3.5%; 95% confidence interval, 0.8–10.2) patients, a 50% to 69% stenosis in 2 (2.3%; 95% confidence interval, 0.1–8.6) patients, and a ≥70% stenosis in 14 (16.3%; 95% confidence interval, 9.8–25.6) patients. A near or persistent occlusion was present in the remaining 52 (60.5%) patients. Conclusions—: A residual high-grade stenosis of the extracranial ICA occurs in 1 of 6 patients with a symptomatic occlusion in the acute stage of cerebral ischemia. Because this may have implications for secondary prevention, we recommend follow-up imaging in these patients within a week after the event. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00880113. Abstract : Supplemental Digital Content is available in the text.